Analyzing Learning Autonomy in Reading English Text at MTS DDI AS-Salman Sidrap - Asiza Syarif; Haris Sunubi (EDUVELOP, 2019)
This research is aimed at investigating the implementation of autonomous learning. Autonomous learning consists of three aspects: self-planning, self-monitoring, and self-evaluating. This research is a use a mixed-method sequential explanatory design. The subject of the research is 24 students of the first grade students of junior high school. The writer observed the classroom, and also gave a set of questionnaire to the students to find out whether they are an autonomous learner or not. The result showed that in self-planning aspect, 56.83% students are self-planned; they are categorized into â€œpoorâ€. In self-monitoring aspect, 81.85% students are self-monitored; they are categorized into â€œgoodâ€. In self-evaluating aspect, 62.53% students are self-evaluated; they are categorized into â€œfairâ€. So, the students got good category in self-monitoring aspect, whereas for self-planning and self-evaluating must be improved.